Thrombotic microangiopathy in a very young infant with mitral valvuloplasty - Yuka Matsunaga; Masataka Ishimura; Hazumu Nagata; Kiyoshi Uike; Tadamune Kinjo; Masayuki Ochiai; Kenichiro Yamamura; Hidetoshi Takada; Yoshihisa Tanoue; Masaki Hayakawa; Masanori Matsumoto; Toshiro Hara; et al. (Elsevier, 2018)
Background: Thrombotic microangiopathies (TMA) are microvascular occlusive disorders characterized by systemic or intrarenal platelet aggregation, thrombocytopenia, and red cell fragmentation. Post-operative TMA mostly occurs in adult patients with cardiovascular surgery, with the distinct pathophysiology from classical thrombotic thrombocytopenic purpura (TTP) although the exact pathophysiology remains unclear. Case presentation: A one-month-old infant developed TMA after the initial surgery of double outlet right ventricle. ADAM metallopeptidase with thrombospondin type 1 motif 13 (ADAMTS13) activity was sustained (64%) with the undetectable inhibitor. Von Willebrand factor (VWF) multimer analyses showed absent high-molecular weight multimers. Echocardiography disclosed severe mitral regurgitation. The mitral valve repair 32 days after the initial valvuloplasty led to prompt resolution of TMA. These suggested that TMA occurred in association with valvulopathy-triggered turbulent shear flow, mechanical hemolysis and endothelial damage. The consumption of large VWF multimers might account for the vascular high shear stress shown in Heyde syndrome. Conclusion: The youngest case of post-operative TMA underscores the critical coagulopathy after the first surgical intervention for congenital heart disease. Key words: cardiac surgery, thrombotic microangiopathy, von Willebrand factor multimers